Analisis Tingkat Ketimpangan Dan Karakteristik Sosial Ekonomi Penduduk - Rafly Parenta Bano (EKONOMI & SOSIAL, 2019)
Although the poverty rate continues to decline, the trend of inequality in Merauke Regency tends to fluctuate and increase compared to 2007. Whereas the economic growth of Merauke Regency is consistently above 7 percent in 2011 and the contribution of the agricultural sector reaches a quarter in GRDP. In addition to the lack of research on the level of inequality in Merauke Regency, this research was conducted with the aim to find out the level of population inequality according to the World Bank's size and to understand the socio-economic characteristics of each population group. This study uses descriptive analysis to answer more clearly the purpose of this study. As a result, the level of inequality in Merauke Regency in 2017 is classified as moderate. Meanwhile, the low-income population mostly lives in the village, more likely to allocate income to consume food but less calorie, accept raskin butdid not receive a Social Protection Card. An important finding in this study is that the accessibility of low-income populations to social protection programs is still low. So it is necessary to evaluate the implementation of the program to be on target.